Exploring Zr Influence on Microstructure and Mechanical Property in FeCoNiCrCuZr Eutectic High-Entropy Alloys - Dewangan, Sheetal Kumar; Jain, Reliance; Paswan, Manikant; Patel, Arvind; Samal, Sumanta; Kumar, Vinod; Ahn, Byungmin (Metals and Materials International, 2024)
In the quest for advanced materials with an exceptional combination of properties, the present work entails a comprehensive study of the design and development of FeCoNiCrCuZrx (x = 2.5, 5, 7.5, and 10 at%) eutectic high-entropy alloys (EHEAs) using an integrated approach. The primary objective of this research is to investigate the influence of zirconium (Zr) on the phase, microstructure, and mechanical properties of the FeCoNiCrCuZrx EHEAs. Accordingly, this study employed a combination of alloy design principles, theoretical thermodynamic calculations, and advanced CALPHAD techniques to tailor the composition of FeCoNiCrCuZrx EHEAs. The microstructure of the resulting alloys was characterized using state-of-the-art scanning electron microscopy and energy-dispersive spectroscopy techniques, elucidating the phase formation and distribution of elements at the nanoscale. The structural and microstructural study confirmed the formation of the face-centered cubic (FCC) matrix, Cu-rich FCC, and Laves phases in the studied alloy system. The calculated phase fraction was 76%, 68.9%, 73.6%, and 65% for the matrix phase after the deconvolution of the X-ray diffraction peak. Furthermore, the results revealed that the addition of Zr significantly influenced the hardness enhancement owing to different phase fractions. This integrated approach not only contributes to the understanding of the role of Zr in EHEAs but also opens new avenues for the design of high-performance structural materials. The findings of this study hold promise for applications in aerospace, automotive, and other industries where materials with exceptional strength and durability are required.
Keywords: Advanced materials; Design and Development; Eutectic high entropy alloy; High entropy alloys; Integrated approach; Microstructures and mechanical properties; Phase fractions; Phases transformation; Primary objective; Property; Eutectic high entropy alloy; Hardness; Microstructural evolution; Phase transformation; Zirconium